Alternative dispute resolution: Law & practice - Yaakob, Adnan (CLJ Publication, 2020)
Disputes or conflicts are common in different places and circumstances and may arise among neighbours, workers, customers and suppliers, between organisational units, departments and even across international borders. Disputes between husband and wife, parents and children, neighbours and commercial disputes ought to be resolved amicably. Achieving this would ensure that the relationship would continue to work, this would benefit the parties involved and it would maintain social harmony and cohesion. Hence, an early involvement in the dispute settlement can lead to strengthening relationships and this builds teamwork besides encouraging open communication and cooperative problem-solving, resolves disagreements quickly and concentrates on win-win resolutions. Unresolved disputes or conflicts may have an adverse impact on the relationship between the disputants as well as other effects such as their productivity and commitment towards their work or organisation. Litigation of disputes in the courts are costly, time-consuming with unpredictable outcomes and above all, the adversarial nature of the court would more likely than not leave the parties bitter at its judgment. There are many disputes that may be resolved outside the framework of conventional litigation, with the courts’ role as a last resort after alternative modes such as negotiation, mediation or conciliation had been exhausted yet the parties failed to reach an amicable solution. Alternative Dispute Resolution (ADR) mechanisms are widely adopted in civil and commercial disputes, matrimonial, personal injury, environmental, probate and estate, information technology, negligence claims, shipping, tenancy and labour disputes, among others. It can also be opted in some categories of criminal cases involving complaint against person or property such as assaults, traffic offences and harassment cases, to name but a few. For a good number of disputes such as religious, community, family and labour, ADR is not merely an alternative but the desired mode of dispute resolution. The choice of a suitable ADR mode would depend on the types of disputes, circumstances of the parties, the urgency of resolving the disputes and the financial conditions of the parties. Unlike litigation in court which can be taxing and stressful to many, ADR offers the best mechanism of resolving conflicts amicably beside savings time and expenses. Realising this, the judiciary has time and again encouraged litigants to adopt mediation to resolve civil disputes, making court appearances as a last resort. Mediation is also extensively promoted at the international level and this is evident with the signing of the United Nations Convention on International Settlement Agreements Resulting from Mediation (also known as the Singapore Mediation Convention) in August 2019. The book ‘Alternative Dispute Resolution: Law and Practice’ consists of 44 chapters covering a wide range of subject matters such as civil, criminal, commercial, matrimonial, labour, negligence claims and land disputes, among others. Various practical application of the ADR mechanisms are discussed with reference to specific subject-matters such as Fintech, Islamic banking and finance, and construction disputes, among others. Ombudsmen, online dispute resolution, statutory adjudication under CIPAA and university arbitration are also featured in this book. It is a rich source of scholarly discussion on various aspects of the ADR, contributed by writers who are experts in their respective fields of research. Undoubtedly, this book is a source of reference to all those concerned particularly to the whole legal and non-legal community such as judges, lawyers, ministry officials, ADR practitioners, non-governmental organisations, academicians, students and the general public who could benefit from the valuable lessons in this book without having to refer to several sources. With the invaluable lessons therein, it is ardently hoped that legal academic faculties should emphasise more on conflict resolution skills to advocacy or litigation skills among their would-be lawyers. By familiarising them with this subject, it would create an increase in awareness of the ADR mechanism and to facilitate the development of the skills within the law school community.